Artificial intelligence in local government: enabling artificial intelligence for good governance in UK local authorities - Vogl, T (Oxford Commission on AI & Good Governance, Oxford Internet Institute, University of Oxford, 2021)
In this, OxCAIGG’s second major research output of the year, author Thomas Vogl explores the use of artificial intelligence by UK local authorities. While there have been a number of successful projects related to back-office automation, predictive analytics for decision support, or the use of chatbots for interactions with resident, Vogl finds that governments face important practical challenges in successfully adopting AI. This briefing note identifies three key challenges and three key enablers that local authorities face when working with AI.